Abstract Model Study of Sensor Network Complexity Analysis Method - Hu Ruo (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Sensor Network Composition is a new area involving important technological need. Some of the main difficulties are to correctly describe Interaction Framework and Complexity of Sensor Network Systems. Abstract interaction logic can be seen as a new technique for representing fuzzy Complexity mechanism. In this paper, we have presented a solution to use Complexity of Sensor Network Systems in Sensor Network analysis. We have proposed methods for analyzing Sensor Network based on an abstract interaction definition. The user’s logics are formalized as abstract concepts. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2175